How do you simplify 12-15sqrt6 + 8sqrt6 - 10sqrt36?

2 Answers
Jun 20, 2016

-48-7sqrt(6)

Explanation:

12-15sqrt(6)+8sqrt(6)-10sqrt(36)
=12-15sqrt(6)+8sqrt(6)-10sqrt(6^2)
=12-15sqrt(6)+8sqrt(6)-10*6
=12-15sqrt(6)+8sqrt(6)-60
=12-60+(-15+8)sqrt(6)
=-48-7sqrt(6)

Jun 20, 2016

-48-(7*sqrt(6))

Explanation:

12+(-15*sqrt(6))+(8*sqrt(6))+(-10*sqrt(36))

We know that sqrt(36)=6.

So, 12+(-15sqrt(6))+(8*sqrt(6))+(-60).

12-60=-48

So, -48+(-15sqrt(6))+(8*sqrt(6))

Now, take out sqrt(6) from last two parenthesis.

That would give us -48+(sqrt(6)*(-15+8))

-15+8=-7

So, the answer would be -48-(7*sqrt(6))